Esme Cahill fails spectacularly : a novel - Bostwick, Marie (William Morrow, an imprint of HarperCollins Publishers, 2023)
Esme Cahill thinks she has failed spectacularly: fired from her New York City publishing job, divorced from her husband, and possessing little more than a broken-down car and a pile of unfinished manuscripts, she drives home to Asheville at the request of her late grandmother, Adele, who had begged her, just before she died, to return to the place she grew up. There she discovers the once-charming lakeside retreat run by her family is sliding toward financial ruin, so with the help of her grandfather, George; estranged mother, Robyn; and a travelling chef Dawes (maker of the world's best grilled cheese sandwich) they set to work. In the attic, Esme unearths a trove of museum-worthy art quilts, sewn by Adele. Piecing together the inspiration behind them, Esme discovers a forgotten chapter in her family history and her grandmother's untold story, that of a gifted artist who never received her due.